Analysis of Slang Word Variations in The Youtube Comment Section on Ive’s ‘Attitude’ Music Video - Adhiyana, Alifah Zahra; Djuharie, Otong Setiawan (INDO PUBLISHING, 2025)
This study explores slang words found in the top 100 most-liked comments on the Youtube music video of IVE’s “ATTITUDE”. Employing a descriptive qualitative approach, the data were analyzed based on Allan and Burridge’s (2006) theory of slang classification and functions. The analysis found a total of 15 slang words and categorized it into five types: Fresh and Creative, Flippant, Imitative, Acronym, and Clipping. The findings show that Acronym is the most dominant slang type, while the most common function is to express impression. The results highlight how the original meanings of these slang words shift in digital fandom contexts and how slang is used by K-pop fans not only to convey enthusiasm and emotional responses but also to strengthen social bonds and shared identity in digital spaces. This study contributes to the understanding of language variation in online fan discourse and the role of slang as a tool for expression and solidarity.